Model Order Reduction Applied to Replicate Blast Wave Interaction with Structure - Edison Shehu; Giovanni Marchesi; Luca Lomazzi; Marco Giglio; Andrea Manes (Engineering Proceedings, 2025)
This research explores the application of model order reduction (MOR) techniques for blast wave propagation and mitigation. Blast waves, with their rapid pressure changes and highly nonlinear behavior, pose significant challenges for predictive modeling. MOR, a mathematical dimensionality reduction technique, offers a solution by simplifying the complexity of large-scale dynamical systems described by differential equations. These systems can be computationally expensive to solve through conventional numerical schemes. MOR creates a reduced-order model (ROM) that retains the essential features and behavior of the original system but with fewer degrees of freedom. Unlike traditional high-fidelity simulations that are accurate but computationally expensive, MOR allows for multi-query scenarios. This approach significantly reduces computational demands without sacrificing accuracy, making it a valuable tool for engineers and professionals in safety engineering and defense planning. The study also enables the creation of reduced-order models based on high-fidelity simulations of blast wave interactions with structures, promoting their broader adoption in safety planning and structural assessments.